The breakthrough on evaluation and treatment in incisional hernia with loss of domain - Dailei Qin; Shibo Wei; Jiyu Tian; Zhiwei Guo; Xian Li; Yuhao Yan; Hangyu Li (International Journal of Abdominal Wall and Hernia Surgery, 2019)
Part of the patients with incisional hernia (IH) suffered from constipation or even circulatory impairment, which is called large IH with loss of domain (LOD) or giant IH. For now, there is still controversy about the definition and pathomechanism of the LOD; meanwhile, there is no clear criterion for evaluating and treating patients with LOD. A systematic search of the literature was implemented in PubMed and the Cochrane database by using the keywords “IH, abdominal wall function(AWF), LOD” and got 60 publications finally. First, there is still no unified definition for LOD, but we found that it was translated into a situation that abdominal content can hardly be reduced with AWF deficiency in 2018th Chinese Guidelines. Second, we concluded that poor abdominal wall contraction caused by muscular atrophy or fibrillation after large area aponeurosis released shall be important pathomechanism of LOD. Third, we found that there are different methods for evaluating LOD, while the activity evaluation may be most useful. Finally, component separation technique (CST), bridge repair or utotransplantation have been recommended in many publications for variable condition. The definition of LOD is better to be divided into the functional deficiency and the anatomical defect just like Chinese guidelines. The pathomechanism of LOD was actually based on anatomical destruction of abdominal wall contraction system. The activity evaluation may be the most convenient method mentioned in the publications. CST was strongly recommended to be used in giant hernia, the defect of which can be hardly closed. Patients who have IH with LOD are proposed to receive hernioplasty as early as possible because of the impendency to reconstruct the large defect on the abdominal wall as well as restoration of the AWF. Surgeons may select appropriate CST to repair IH according to the length of the defect.